Recent changes in the feeding of cod (Gadus morhua) off the Flemish Cap, newfoundland 1989-1993 - Casas-Sánchez, José Miguel; Paz, Xabier (ICES Journal of Marine Science, 1996)
La versión completa de este artículo está disponible en la web del editor The food and feeding of Flemish Cap cod are described for 5 years based on 3921 stomachs collected in the fishing grounds off the Flemish Cap, Newfoundland in summer 1989–1993. Feeding intensity was high but the prey spectrum was narrow in all years with hyperiids and redfish (Sebastes sp.) predominating. Squid and poly-chaetes had a high inter-annual variability. Juvenile cod diet was dominated by crustaceans, mainly hyperiids, and polychaetes, while in adult cod diet the most important prey were fish, mainly redfish. The maximum size of redfish eaten increased with cod size, but prey–predator size relationships showed weak correlation. Cannibalism increased in 1991 (mainly upon 1-year-olds), coinciding with the appearance of a large year class in 1990. In the years 1992 and 1993, a change in the diet was observed involving an increase of hyperiids in the adult cod diet and a decline of redfish. peer review